The Effect of (1S,2S,3E,7E,11E)-3,7,11,15-Cembratetraen-17,2-Olide (LS-1) from Lobophyyum sp. on the Apoptosis Induction of SNU-C5 Human Colorectal Cancer Cells - Kim, Eun-Ji (Biomol Ther (Seoul), 2016)
(1S,2S,3E,7E,11E)-3,7,11,15-cembratetraen-17,2-olide (LS-1), a marine cembrenolide diterpene, has anticancer activity against colon cancer cells such as HT-29, SNU-C5/5-FU (fluorouracil-resistant SNU-C5) and SNU-C5. However, the action mechanism of LS-1 on SNU-C5 human colon cancer cells has not been fully elucidated. In this study, we investigated whether the anticancer effect of LS-1 could result from apoptosis via the modulation of Wnt/β-catenin and the TGF-β pathways. When treated with the LS-1, we could observe the apoptotic characteristics such as apoptotic bodies and the increase of sub-G1 hypodiploid cell population, increase of Bax level, decrease of Bcl-2 expression, cleavage of procaspase-3 and cleavage of poly (ADP-ribose) polymerase in SNU-C5 cells. Furthermore, the apoptosis induction of SNU-C5 cells upon LS-1 treatment was also accompanied by the down-regulation of Wnt/β-catenin signaling pathway via the decrease of GSK-3β phosphorylation followed by the decrease of β-catenin level. In addition, the LS-1 induced the activation of TGF-β signaling pathway with the decrease of carcinoembryonic antigen which leads to decrease of c-Myc, an oncoprotein. These data suggest that the LS-1 could induce the apoptosis via the down-regulation of Wnt/β-catenin pathway and the activation of TGF-β pathway in SNU-C5 human colon cancer cells. The results support that the LS-1 might have potential for the treatment of human colon cancer.